(untitled) (Research, Society and Development, 2022)
This research aims to understand how Trichomonas vaginalis is a sexually transmitted disease as well as the human papillomavirus that is the cause of precursor lesions and cervical cancer. Taking into account the relationship between both, which allows the protozoan to act as a facilitator of HPV infections. This is an integrative review, in which data collection was verified with articles between 2014 and 2022 in the following databases: Scientific Electronic Library Online (Scielo), Virtual Health Library (BVS), JmolMed, Report in Public Health, Scientific reports, The Journal of Infection in Developing Countries and Publisher Medline (PubMED), using the following descriptors and keywords: Trichomonas vaginalis, Human Papillomavirus, Precursor Lesions and Cervical Cancer. Proof of the presence of Trichomonas vaginalis in precursor lesions and cervical cancer. It was concluded that there is an infectious relationship between Trichomonas vaginalis in establishing an environment for the persistence and permanence of Human Papillomavirus in precursor lesions and cervical cancer.